Numerical investigation of initial crack growth in composite laminates under tension - Dubovikov Evgeny; Shanygin Alexander; Vedernikov Dmitry (MATEC Web of Conferences, 2019)
The simplified automated strength model of a fragment of composite laminate at microlevel based on the finite elements (FE) method is offered. The model allows investigating the growth of microcracks which arise in the resin in monolayers, orthogonal to a direction of external tensile force. On the basis of automated strength FE model of a fragment of composite laminate and the method of reduction of stiffness characteristics of the resin, the scenario of growth of primary destructions at the microlevel is offered and proved. The scenario is confirmed with experimental investigations of composite samples under tension with registration of acoustic emission. In the work, the dependences of decrease of strength characteristics of composite laminates are obtained as functions of characteristics of resin, angles of orientation of monolayers, volume ratio of fibres in a composite laminate.